2008
DOI: 10.1007/s00542-007-0492-0
|View full text |Cite
|
Sign up to set email alerts
|

Hot embossing of microstructures: characterization of friction during demolding

Abstract: Today, hot embossing and injection molding belong to the established plastic molding processes in microengineering. Based on experimental findings, a variety of microstructures have been replicated so far using the above processes. However, with increasing requirements regarding the embossing surface and the simultaneous decrease of the structure size down into the nanorange, increasing know--how is needed to adapt hot embossing to industrial standards. To reach this objective, a GermanCanadian cooperation pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 7 publications
0
34
0
1
Order By: Relevance
“…It is governed by the elastic or viscoelastic properties of the polymer, the relative velocity of the surfaces (the demolding rate), and also the overall pressure distribution. Worgull et al (2008a) have published results of simulated replication trials where various demolding rates were studied. Static coefficients of friction at 1 mm/min were substantially higher than those at 5 mm/min.…”
Section: Hysteresismentioning
confidence: 99%
“…It is governed by the elastic or viscoelastic properties of the polymer, the relative velocity of the surfaces (the demolding rate), and also the overall pressure distribution. Worgull et al (2008a) have published results of simulated replication trials where various demolding rates were studied. Static coefficients of friction at 1 mm/min were substantially higher than those at 5 mm/min.…”
Section: Hysteresismentioning
confidence: 99%
“…또한 측벽의 표면 거칠기에 따라 이형력에 차이가 있음이 연구되었다 [2] . Yuhua Guo [3,4] 은 ABAQUS/Standard을 사용하여 Hot embossing 공정에서 금형과 polymer의 수축차이로 인한 열응력에 대하여 연 .…”
Section: 서 론unclassified
“…Worgull et al [6,28] observed that demoulding forces may vary by several factors depending on the process parameters selected and the quality of the tool. A test apparatus which can be used in a tensile testing machine was described and results presented based on varying parameters.…”
Section: Determining a Suitable Coefficient Of Frictionmentioning
confidence: 99%